2018
DOI: 10.1093/pubmed/fdy080
|View full text |Cite
|
Sign up to set email alerts
|

Time trend and regional variability of mortality rate due to ovarian cancer in Brazil: a 15-year analysis

Abstract: Although there are oscillations in mortality rates of OC in Brazil and its regions over the period studied, this parameter has remained relatively stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
0
0
1
Order By: Relevance
“…It occurs bilaterally in 30-50% of patients, affects women close to 60 years of age, is generally diagnosed late, and results in high lethality. In the context of late diagnosis and high lethality [9], studies on tumor biomarkers are very important for the prevention and early detection of ovarian cancer [3,6], as well as for analyzing social and demographic aspects to track the most vulnerable population and better understand the etiology of ovarian cancer [1,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs bilaterally in 30-50% of patients, affects women close to 60 years of age, is generally diagnosed late, and results in high lethality. In the context of late diagnosis and high lethality [9], studies on tumor biomarkers are very important for the prevention and early detection of ovarian cancer [3,6], as well as for analyzing social and demographic aspects to track the most vulnerable population and better understand the etiology of ovarian cancer [1,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding mortality, a study based on the Global Cancer Observatory (GLOBOCAN) database showed that mortality rates vary among different countries due to differences in the Human Development Index (HDI) [2]. According to the National Cancer Institute (INCA), in Brazil, ovarian cancer is considered a gynecologic neoplasm with the lowest chance of cure, because of the challenges in diagnosis and the lack of an appropriate screening method to detect the disease at an early stage [3]. In this context, the discovery of a biomarker considering the histological subtypes of ovarian cancer may help identify individuals at a higher risk and/or detect the disease at an early stage.…”
Section: Introductionmentioning
confidence: 99%
“…(AUGUSTO et al, 2018;FERREIRA et al, 2018;JANOVSKY et al, 2018;LUCIANO et al, 2018;PAIVA;SOUZA, 2018;TEIXEIRA et al, 2018b;ALMEIDA et al, 2019ALMEIDA et al, , 2019BESSA;BONATTO, 2019;HERTZ et al, 2019;SENGER;SANTAREM;GOLDMEIER, 2019). Outra variável muito analisada nas pesquisas foi a região estudada, pois a prevalência de algumas condições e os investimentos em saúde influenciam de forma expressiva nos dados (BOQUETT et al, 2018;FERNANDES et al, 2018;PAVANITTO;MENEZES;NASCIMENTO, 2018;SCHOUERI et al, 2018;TEIXEIRA et al, 2018a;KUPEK, 2018).…”
Section: Estratégias De Pesquisaunclassified